COVID-19 vaccination in 5-11 years old children: Drivers of vaccine hesitancy among parents in Quebec - Eve Dubé; Dominique Gagnon; Catherine Pelletier (Taylor & Francis Group, 2022)
The Pfizer-BioNTech COVID-19 vaccine was recently authorized for Canadian children aged 5 to 11 years old. Previous studies have indicated that low parental vaccination intention can be anticipated. To better understand drivers of vaccine hesitancy among parents of 5-11 years old children, four focus group discussions were conducted. Interviewed parents generally showed little concern about the risk of COVID-19 for their child(ren) and many mentioned that children are at low risk of complications from COVID-19. Out of 28 participants, seven intended to vaccinate their child(ren) while the remaining were unsure or unwilling. Even if parents were themselves vaccinated, many hesitated for their child(ren). These parents perceived that it was unnecessary (due to low risk of complications) and were concerned about risks of side effects. Clear communication on vaccine safety and usefulness will be critical to reassure parents and foster vaccine acceptance.